مصادر الشريعة المسيحية الحالية - جبار رحاب حسين (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
This study reviews the major sources of current Christian law, explaining the frameworks that guide the lives of believers through religious, ethical, and spiritual perspectives. The Bible is the primary source of Christian law, including the Old and New Testaments, and is considered the inspired word of God that contains Christ’s teachings and message. Church tradition is another important source, and includes teachings accumulated over the centuries from the decisions of the Ecumenical Councils and the writings of the Church Fathers, which helps in interpreting the Bible and applying its teachings. Reason plays a vital role in interpreting and understanding sacred texts and church tradition, as Christian thought encourages the use of reason to solve contemporary issues and provide new insights. The personal and communal experience of believers, including experiences of the Holy Spirit, is an integral part of Christian law, contributing to understanding and applying God’s will through prayer, worship, and social service. By integrating Scripture, tradition, reason and experience, Christian law takes shape as a comprehensive system that directs the lives of believers toward the principles of love, service, and devotion to God and humanity, helping them to live out the principles of their faith and the challenges of the modern age